IMPLEMENTING THE BSC APPROACH IN RESPONSE TO STRUCTURAL POLICY CHALLENGES IN INDONESIA: A CASE STUDY OF THE MINISTRY OF FINANCE'S LEADERSHIP PERSPECTIVES - Budiarso, Adi (Badan kebijakan Fiskal, 2013)
One tool used for strategic performance management in the public sector organisations is the Balanced Scorecard (BSC) approach. The BSC can assist the definition of comprehensive strategic objectives, better key performance indicators and improved organisational performance outcomes. The BSC system not only promotes synergy and alignment of strategies among that of departmental and functional units, but also it promotes strategic communication for decision-makers to sustain high organisational performance outcomes. Based on the leadership accountability framework as a means to analyse the process of improving and sustaining public sector performance outcomes, this study also found that four key elements contributed to the successful implementation of the BSC to improve and sustain public sector performance: leadership effectiveness, strategy and HRM